The Evolution of Accounting Standards After the Financial Crisis: Effects of the Digital Age - Kermani, Zahra; Karimi, Darya (International Journal of Business Management and Entrepreneurship, 2025)
This study explores the dynamic evolution of accounting standards in the aftermath of the 2007–2008 global financial crisis, emphasizing the transformative influence of the digital age on financial reporting practices. The crisis exposed critical flaws in fair value accounting, risk disclosure, and the timeliness of financial information, prompting substantial reforms in international accounting standards, including IFRS and GAAP frameworks. In parallel, the rapid emergence of digital technologies—such as blockchain, artificial intelligence, big data analytics, and cloud computing—has redefined the scope and execution of accounting practices. Through a comprehensive literature review and empirical insights, the study illustrates how regulatory bodies, financial institutions, and accounting professionals have adapted to a complex environment shaped by both post-crisis reforms and technological advancements. The integration of real-time data processing, digital asset reporting, algorithmic auditing, and enhanced cybersecurity protocols has become essential to modern accounting. Furthermore, the study highlights the growing significance of non-financial disclosures, especially ESG and sustainability-related data, in aligning accounting standards with the evolving needs of global stakeholders. The findings indicate that the future of accounting lies in a flexible, principle-based, and technologically integrated framework that balances innovation with transparency and accountability. The study concludes with forward-looking recommendations for regulators, educators, and practitioners to ensure that accounting standards remain relevant, resilient, and ethically grounded in an increasingly digital financial ecosystem.